Shelf life extension of mozzarella cheese packed in preserving liquid with calcium lactate and bergamot juice concentrate. Issue 4 (10th November 2020) - Zappia, Angela; Branca, Maria Luisa; Piscopo, Amalia; Poiana, Marco
Abstract: Traditional Mozzarella is a fresh cheese produced in Italian local market without additives that shows a short shelf life of about 5 d. This work tested the use of natural additives (bergamot juice concentrate-BJ and calcium lactate-CL) in preserving liquid for a Mozzarella cheese with the aim to extend its shelf life, regarding the microbial growth and overall cheese quality. Results of qualitative analyses showed that the preserving liquid with the mix of BJ and CL promoted an extension of mozzarella shelf life up to 20 d. A slightly reduced growth of Pseudomonas species was evidenced after 5 d of storage, whereas no inhibition of lactic acid bacteria was observed for the storage period. Moreover, mozzarella cheese packed in mixed preserving liquid possessed better textural properties, evidenced by the lowest proteolysis index measured after 13 d of storage, and a good antioxidant activity.